Implementasi Kebijakan Dinas Kependudukan dan Pencatatan Sipil Kabupaten Ciamis dalam Penyelenggaraan Administrasi Kependudukan Melalui Aplikasi Pelayanan Cepat Aman dan Ramah - Cantika Mutiara K; Arie Budiawan; Abdul Mutholib (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
On the research of background, it is analyzed that the Implementation of the Population Administration Policy Through a Fast, Safe and Friendly Service System at the Population and Civil Registration Office of Ciamis Regency. The purpose of this study is to determine the implementation of the Si Lancer application service at the Population and Civil Registration Service of Ciamis Regency. This research method uses descriptive qualitative with data collection techniques through interviews, observation, and documentation. The results of the study indicate that the Implementation of the Population Administration Policy Through a Fast, Safe and Friendly Service System at the Population and Civil Registration Office of Ciamis Regency is not optimal, namely constrained by human resources in the Office, lack of facilities at the Population and Civil Registration Office of Ciamis Regency, lack of implementing attitudes where employees prefer conventional services, no application updates from the initial year of publication, namely 2021, and no fragmentation or group bodies specifically tasked with Si Lancar application services. This study contributes to broadening understanding of the practical benefits of implementing the use of the Si Lancar application at the Population and Civil Registration Office of Ciamis Regency.